2020
DOI: 10.1111/bcpt.13483
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic studies of thiopurine methyltransferase genotype‐phenotype concordance and effect of methotrexate on thiopurine metabolism

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…As an antifolate, MTX inhibits several folate-dependent enzymes whose function is central to thymidylate and de novo purine biosynthesis and in one-carbon metabolism, affecting amino acid metabolism, and mitochondrial protein synthesis. [19][20][21] Ideally, the combination of MP and MTX in maintenance is synergic and safe to provide the required long-term mild suppression with minimal adverse effects on bone marrow. Planned MP and MTX doses vary according to international protocols (e.g., MP: 50 mg/m 2 /day in the Associazione Italiana di Ematologia e Oncologia Pediatrica (AIEOP)-Berlin-Frankfurt-Muenster (BFM) protocol and 75 mg/m 2 /day in St. Jude Children's Research Hospital (SJCRH) Total XVII and Children's Oncology Group (COG) trials).…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…As an antifolate, MTX inhibits several folate-dependent enzymes whose function is central to thymidylate and de novo purine biosynthesis and in one-carbon metabolism, affecting amino acid metabolism, and mitochondrial protein synthesis. [19][20][21] Ideally, the combination of MP and MTX in maintenance is synergic and safe to provide the required long-term mild suppression with minimal adverse effects on bone marrow. Planned MP and MTX doses vary according to international protocols (e.g., MP: 50 mg/m 2 /day in the Associazione Italiana di Ematologia e Oncologia Pediatrica (AIEOP)-Berlin-Frankfurt-Muenster (BFM) protocol and 75 mg/m 2 /day in St. Jude Children's Research Hospital (SJCRH) Total XVII and Children's Oncology Group (COG) trials).…”
Section: Articlementioning
confidence: 99%
“…MTX is conjugated intracellularly to polyglutamates and thus remains trapped inside the cells. As an antifolate, MTX inhibits several folate‐dependent enzymes whose function is central to thymidylate and de novo purine biosynthesis and in one‐carbon metabolism, affecting amino acid metabolism, and mitochondrial protein synthesis 19–21 . Ideally, the combination of MP and MTX in maintenance is synergic and safe to provide the required long‐term mild suppression with minimal adverse effects on bone marrow.…”
mentioning
confidence: 99%
“…Sec is an analogue of the more common amino acid cysteine, with the essential trace element selenium in place of the sulfur, and is now considered as the 21st "naturally occurring" amino acid encoded by the a noncanonical translation of the UGA codon (as revised by Labunskyy VM and collaborators) [20]. By investigating in vitro the activity of recombinant TPMT on selenium-containing amino acids through saturation transfer difference and 77 Se nuclear magnetic resonance spectroscopy, fluorescence measurements, as well as computational molecular docking simulations, Urbančič and coworkers demonstrated that methylation of Sec occurred in a SAM-dependent manner. A direct interaction between Sec and SAM in the active site of recombinant TPMT was observed, and both methylated-Sec and SAH were detected as reaction products [19].…”
Section: Tpmt Enzyme and Functionmentioning
confidence: 99%
“…In the treatment of leukemia, MTX is often used alongside MP [76]. A synergistic effect between MTX and MP has been shown in vitro and in vivo, and is believed to be associated to the inhibitory effect of MTX on purine de novo synthesis and pyrimidine synthesis [77,78]. As folate analogue, MTX and its polyglutamate metabolites (MTX-PG) interfere with enzymes of the folate pathway, which are interconnected to many other synthetic pathways.…”
Section: Tpmt Enzymatic Activity and Thiopurine Effects: Other Contri...mentioning
confidence: 99%
“… 18 Both intermediate-deficient and poor TPMT metabolizers have an increased risk of developing life-threatening myelosuppression upon receiving standard doses of thiopurine drugs. 19 They may also experience unexpected myelosuppression when they have been administrated the recommended doses of 6-MP. Given these findings, the Clinical Pharmacogenetics Implementation Consortium (CPIC) has provided guidelines and recommendations for dosing individuals carrying TPMT-deficient alleles.…”
Section: Introductionmentioning
confidence: 99%